Pervious concrete prepared from modified recycled aggregate and nano reinforced material
Through the combination of modified regenerated aggregate and nanoreinforced materials, combined with intelligent hybrid optimization systems and self-healing microcapsules, the problem of insufficient mechanical properties of existing permeable concrete in high-strength application scenarios is solved, and higher mechanical properties and better environmental adaptability are achieved.
Patent Information
- Application Number
- CN202411772612.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
AI Technical Summary
The existing permeable concrete has insufficient mechanical properties in high-strength application scenarios, and the quality of regenerated aggregates is unstable, making it difficult to meet diverse engineering application scenarios and performance requirements. At the same time, the spectral utilization rate of nano-TiO2 materials is low, which affects the self-cleaning and anti-fouling functions of concrete.
Permeable concrete is prepared by modified regenerated aggregate and nanoreinforced materials. The binding force with the cement matrix is enhanced by modifying the surface of the regenerated aggregate (such as acid etching and high-temperature heat treatment), and the nanoreinforced materials are evenly dispersed through ultrasonic vibration treatment technology. At the same time, an intelligent hybrid optimization system and self-healing microcapsules were introduced, and the material ratio was automatically adjusted according to environmental factors, and a photocatalytic purification device was used during the maintenance process.
It significantly improves the mechanical properties of permeable concrete, can meet the requirements of high-strength application scenarios, extends the service life of concrete, and improves its adaptability and pollution resistance under different environmental conditions.
Smart Images

Figure CN119591365A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a permeable concrete prepared from modified recycled aggregate and nano-reinforced material. Background Art
[0002] With the acceleration of urbanization and the large-scale development of infrastructure construction, the demand for concrete in the construction industry continues to rise. At the same time, traditional methods of disposing construction waste are mostly landfill or stacking, which not only occupies a large amount of land resources, but also may cause serious pollution to the soil, water and other ecological environments.
[0003] As an environmentally friendly building material, permeable concrete has good permeability, can effectively alleviate the problem of urban rainwater runoff, replenish groundwater, and has been used in urban roads, squares, parking lots and other projects. In terms of aggregates, ordinary recycled aggregates have a lot of impurities and old cement slurry layers on the surface, resulting in poor bonding performance with the cement matrix, making it difficult for the mechanical properties of permeable concrete to meet some engineering application scenarios with higher strength requirements, such as heavy-loaded traffic roads. In addition, the quality of recycled aggregates is unstable and is greatly affected by the source and processing technology, which further limits its wide application in high-performance permeable concrete.
[0004] According to the Chinese patent number CN118955046A, a permeable concrete based on recycled aggregate loaded with nano TiO2 and its preparation method, which belongs to the field of concrete material technology, includes the following mass components: 350-400 parts of natural aggregate, 200-250 parts of recycled aggregate, 210-230 parts of cement, 240-260 parts of spun yarn, 60-90 parts of mineral powder, 12-15 parts of reinforcing material, 10-20 parts of composite nano titanium dioxide photocatalytic material, 0.8-1 parts of sodium tripolyphosphate, 5-10 parts of water reducer, and 250-270 parts of water. The hollow nanomaterial loaded with nano titanium dioxide is filled between the nanosheet layers to form a concave-convex layer structure, which increases the reflection and reflection distance of visible light; the fish scale powder and the recycled aggregate are combined through hydrogen bonds, which can connect the recycled aggregate to form a more effective stress transfer network, and prevent the concrete from being affected by environmental factors, wear, rain erosion, etc., which causes the nano photocatalytic material to fall off easily.
[0005] The following problems exist in the production process of the existing technology: 1. Although the existing patents use recycled aggregates loaded with nano-TiO2 and other materials, the amount of recycled aggregates is relatively small compared to natural aggregates, and the capacity to absorb a large amount of construction waste is limited, and the advantages of recycled aggregates in resource recycling and environmental protection are not fully utilized. At the same time, the proportion of each component in its ratio is relatively fixed, lacking a mechanism for flexible adjustment according to different engineering needs and environmental conditions, and it is difficult to meet the diverse engineering application scenarios and performance requirements; 2. Although the existing patents mention that the loaded nano-titanium dioxide hollow nanomaterials can form a concave-convex layer structure to increase visible light reflection, etc., the nano-TiO2 material itself has the problem of low solar energy spectrum utilization, which limits its photocatalytic performance and thus affects the self-cleaning and anti-fouling functions of concrete; 3. The existing technology does not mention the adaptability of material ratios and performance to changes in different environmental factors, so a permeable concrete prepared by modified recycled aggregates and nano-reinforced materials is needed to solve the above problems. Summary of the invention
[0006] 1. Technical issues to be resolved
[0007] In view of the shortcomings of the prior art, the present invention provides a permeable concrete prepared from modified recycled aggregates and nano-reinforced materials, the composition of which includes recycled aggregates (including waste concrete, brick and tile waste, ceramic fragments and glass waste), nano-reinforced materials (such as nano-silicon dioxide, nano-clay, nano-titanium oxide, nano-carbon tubes, etc.), silicate cement matrix, polycarboxylate water reducer, sodium dodecylbenzene sulfonate surfactant and water, and the mass ratio of each component is within a specific range.
[0008] The particle surface of the recycled aggregate undergoes a multi-step modification treatment. First, it is thoroughly cleaned to remove impurities, then the residual cement slurry layer is removed by acid etching with hydrochloric acid solution and the microstructure is improved. Then, high-temperature heat treatment is used to further remove moisture and residual harmful substances, while enhancing the surface hardness, thereby improving the bonding strength between the recycled aggregate and the cement matrix. When preparing nano-reinforced materials, nano-silicon dioxide is evenly dispersed in the cement matrix with the help of ultrasonic vibration processing technology. In the mixing process of recycled aggregate and nano-reinforced materials, a high-efficiency mixer is used with an intelligent mixing optimization system. The system automatically adjusts the material ratio according to environmental factors such as temperature and precipitation, and self-repairing microcapsules are added to the concrete, which can be repaired in time when microcracks appear. After the mixed material is formed by a standard template, it is compacted by a vibration table. The formed concrete is placed in a curing room with controlled temperature and humidity for curing. During this period, the hardening progress and strength growth are closely monitored. Various methods such as water permeability coefficient test, compressive strength test, freeze-thaw cycle test, etc. are also used to ensure that the various properties such as permeability, compressive strength, and frost resistance meet the requirements.
[0009] (II) Technical solution
[0010] To achieve the above objectives, the present invention is implemented by the following technical scheme: a permeable concrete prepared by modified recycled aggregate and nano-reinforced material, comprising recycled aggregate, nano-reinforced material, cement matrix, water reducer, surfactant and water, wherein the recycled aggregate comprises waste concrete, brick and tile waste, ceramic fragments and glass waste, the nano-reinforced material comprises nano-silicon dioxide, nano-clay, nano-titanium oxide and nano-carbon tube, the particle surface of the recycled aggregate is modified, the recycled aggregate and the nano-reinforced material are The mass ratio of the recycled aggregate, the nano-reinforced material, the cement matrix, the water reducer, the surfactant and water is 1:0.1 to 1:0.5:0.3 to 0.5:0.05 to 0.1:0.02 to 0.05:0.4 to 0.6, and the particle surface of the recycled aggregate is modified, and the modification process comprises the following steps:
[0011] Sp1. Surface modification treatment steps of recycled aggregate: select waste concrete, brick and tile waste, ceramic fragments and glass waste, and thoroughly clean them to remove dirt and grease attached to the surface. During the cleaning process, use a combination of high-pressure water flow and physical brushing to ensure that the surface of each particle is clean. Soak the cleaned aggregate in a hydrochloric acid solution with a concentration of 5% to 10% for acid etching to remove the residual cement slurry layer on the surface of the aggregate, peel off the excess cement layer through chemical reaction, and improve the surface microstructure of the aggregate. The acid etching time is 30 to 60 minutes, and the temperature is controlled within the normal temperature range to prevent damage to the aggregate due to excessive reaction. After acid etching, place the aggregate in a high temperature environment of 350°C to 500°C for heat treatment for 1 to 2 hours. Through high temperature treatment, remove moisture and residual harmful substances in the aggregate, and further enhance the surface hardness of the aggregate, and improve the bonding strength between the recycled aggregate and the cement matrix;
[0012] SP2, preparation steps of nano-reinforced materials: the nano-reinforced materials can be selected from nano-silicon dioxide, nano-clay and nano-carbon tubes. When nano-silicon dioxide is selected, it forms a stable hydration product with the cement matrix through good surface activity to enhance the strength and durability of concrete. Ultrasonic vibration treatment technology is used to ensure that the nano-silicon dioxide and the cement matrix are evenly dispersed. The ultrasonic power is 200-600W, and the vibration time is 3 to 5 minutes. The mass ratio of the nano-silicon dioxide is 0.5% to 2% of the cement matrix, the mass ratio of the nano-clay is 0.1% to 0.5% of the cement matrix, and the mass ratio of the nano-carbon tube is 0.05% to 0.2% of the cement matrix;
[0013] SP3, the step of mixing recycled aggregate and nano-reinforced material: the recycled aggregate and nano-reinforced material are stirred by a high-efficiency mixer during mixing, the stirring time is 5 to 10 minutes, and the stirring speed is 30 to 50 rpm. An intelligent mixing optimization system is established to assist the mixing of recycled aggregate and nano-reinforced material. The intelligent mixing system automatically adjusts the material ratio according to the two environmental conditions of temperature change and precipitation through machine learning and multi-objective optimization algorithm to ensure that the permeable concrete has the best comprehensive performance. The intelligent mixing optimization system collects temperature and precipitation data through temperature sensors and rainfall sensors in real time, analyzes environmental data through machine learning algorithms and optimization decision algorithms, and calculates the appropriate material ratio. Self-repairing microcapsules are added to the concrete. When microcracks appear in the concrete, the microcapsules rupture and release the repair agent, which reacts with the cement matrix to repair the cracks and extend the service life of the concrete.
[0014] SP4, the mixed material produced by mixing the recycled aggregate and the nano-reinforced material in SP3 is molded through a standard template, the size of the mold is 300mm×300mm×50mm, and a vibration table is used for vibration compaction, the vibration frequency is 20-30Hz, and the vibration time is 30 seconds to 1 minute, to ensure that the surface of the molded concrete is flat and there are no pores inside. The molded concrete is placed in a curing room with controlled temperature and humidity for curing. The curing temperature should be maintained between 20°C and 30°C, and the humidity is controlled at more than 90%. The curing time is 7 to 14 days. During this period, the hardening progress and strength growth of the concrete are monitored, and a temperature control curing system is used to automatically adjust the temperature and humidity, accelerate the hydration reaction, and improve the strength of the concrete. During the curing period, a temperature and humidity sensor is used to monitor the internal temperature and humidity of the concrete, and the curing conditions are adjusted in real time;
[0015] SP5. Use the water permeability coefficient test method to test the permeability of permeable concrete. During the test, place the concrete sample in a water leaker, measure the time for water to pass through the concrete, calculate the water permeability coefficient, and ensure that the permeability meets the national standards. Then, conduct a compressive strength test according to the national standards. The compressive strength of the test sample should be greater than 25MPa. During the test, use a hydraulic testing machine to apply pressure to the standard specimen until it is destroyed, and record the maximum bearing capacity. Place the sample in a freeze-thaw test box and perform 25 freeze-thaw cycles to observe the mass loss rate and frost resistance changes of the sample. At the same time, monitor the crack width and crack extension to ensure the long-term stability of permeable concrete in cold areas.
[0016] Preferably, after acid etching, the recycled aggregate is further modified on its surface by plasma treatment technology, the plasma treatment power is 100-300W, and the treatment time is 10-20 minutes. The plasma treatment increases the surface active groups and improves the bonding strength with the nano-reinforcement material and the cement matrix.
[0017] Preferably, the nano-reinforcement material also includes a nano-metal oxide mixture, which is composed of nano-zinc oxide and nano-magnesium oxide in a mass ratio of 1:1-3:1, and its total mass ratio in concrete is 0.1%-0.3% of the cement matrix, thereby improving the concrete's anti-ultraviolet aging performance.
[0018] Preferably, in the step of mixing the recycled aggregate and the nano-reinforcement material, a bio-based additive is added, the bio-based additive is sodium lignin sulfonate and can also be cellulose ether, the mass ratio of which is 0.02%-0.1% of the cement matrix, so as to improve the working performance of the concrete and enhance its environmental friendliness.
[0019] Preferably, the intelligent mixing optimization system can automatically adjust the content of nano-titanium dioxide in the nano-reinforcement material according to the ultraviolet intensity data, the ultraviolet intensity data is collected by the ultraviolet sensor, and when the ultraviolet intensity increases, the nano-titanium dioxide content is increased to enhance the anti-ultraviolet ability of the concrete, and the content adjustment range is 0.05%-0.15% of the cement matrix mass ratio.
[0020] Preferably, the repair agent in the self-repairing microcapsule contains a polymer emulsion and an inorganic mineral material, the polymer emulsion is an acrylic emulsion, and the inorganic mineral material is wollastonite powder, and the mass ratio of the two is 2:1-3:1, which can more effectively repair concrete microcracks and enhance the strength of the repaired part.
[0021] Preferably, a photocatalytic purification device is provided in the curing room, and the concrete surface is photocatalytically treated during the curing process to remove pollutants on the surface. The photocatalytic purification device uses a nano-titanium dioxide photocatalyst, and the wavelength of the ultraviolet light source is 250-350nm.
[0022] Preferably, during the concrete forming process, a layer of release agent is coated on the inner surface of the mold, and the release agent is a water-based fluorocarbon release agent, which effectively reduces the adhesion between the concrete and the mold and ensures the integrity and smoothness of the concrete surface after forming.
[0023] Preferably, 5%-10% fly ash is added to the cement matrix, and the average particle size is 10 μm.
[0024] (III) Beneficial effects
[0025] The present invention provides a permeable concrete prepared by modified recycled aggregate and nano-reinforced material, which has the following beneficial effects:
[0026] In the present invention, modified recycled aggregate and nano-reinforced materials are used, especially after acid etching and plasma treatment on the surface of the recycled aggregate, the bonding performance between the recycled aggregate and the cement matrix is enhanced, and the mechanical properties of the permeable concrete are significantly improved. This modification ensures that the permeable concrete can meet higher performance requirements in high-intensity application scenarios (such as heavy-load traffic roads), and can maintain good stability and durability during long-term use, avoiding cracks or damage in traditional permeable concrete under stress.
[0027] The present invention uses waste building materials (such as waste concrete, brick and tile waste, ceramic fragments, etc.) as recycled aggregates, and combines them with nano-reinforced materials to improve their performance, which not only effectively solves the problem of traditional construction waste disposal, but also promotes the reuse of resources and reduces dependence on natural aggregates. This innovation provides an environmentally friendly material option for urban construction, reduces the occupation of land resources, and effectively reduces environmental pollution.
[0028] The permeable concrete formula of the present invention can dynamically adjust the proportion according to different environmental factors (such as temperature, precipitation and ultraviolet intensity, etc.) by introducing an intelligent mixing optimization system, thus achieving the best performance of permeable concrete in different application scenarios. This system can not only optimize the use of materials, but also improve the self-repairing ability and anti-fouling ability of concrete through self-repairing microcapsules and photocatalytic purification devices, extend the service life of concrete, and enhance its ability to adapt to different environmental changes. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a logical framework diagram of the preparation process of the present invention;
[0030] Figure 2 is a preparation flow chart of the present invention;
[0031] Figure 3 This is a simulation diagram of the optimized permeable concrete mix ratio of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Specific embodiment one:
[0034] like Figure 1-3As shown, a permeable concrete prepared by modified recycled aggregate and nano-reinforcement material comprises recycled aggregate, nano-reinforcement material, cement matrix, water reducer, surfactant and water, the recycled aggregate comprises waste concrete, brick and tile waste, ceramic fragments and glass waste, the nano-reinforcement material comprises nano-silicon dioxide, nano-clay, nano-titanium oxide and nano-carbon tube, the particle surface of the recycled aggregate is modified, the mass ratio of the recycled aggregate to the nano-reinforcement material is 1:0.05 to 1:0.15, the cement matrix is silicate cement, the water reducer is a polycarboxylate water reducer, the surfactant is sodium dodecylbenzene sulfonate, the recycled aggregate The mass ratio of the material, nano-reinforcement material, cement matrix, water reducer, surfactant and water is 1:0.1 to 1:0.5:0.3 to 0.5:0.05 to 0.1:0.02 to 0.05:0.4 to 0.6. When the recycled aggregate is taken as the reference mass part and is set to 1 part, the amount of the nano-reinforcement material is 0.1-0.5 part, the amount of the cement matrix is 0.3-0.5 part, the amount of the water reducer is 0.05-0.1 part, the amount of the sodium dodecylbenzene sulfonate surfactant is 0.02-0.05 part, and the amount of water is 0.4-0.6 part. The particle surface of the recycled aggregate is modified.
[0035] When selecting waste concrete as recycled aggregate, concrete blocks from abandoned building structures with a service life of 5-15 years are preferred, because the aggregate formed after crushing and other treatments of concrete in this age range has a relatively stable internal structure and a certain residual strength, which can better meet the mechanical performance requirements of permeable concrete. For brick and tile waste, it is necessary to classify and screen them, remove the parts containing a large amount of impurities or severely weathered, and only select brick and tile fragments with relatively hard texture and complete structure to ensure the stability of the overall quality of recycled aggregate. The maximum particle size of ceramic fragments and glass waste should be controlled to ensure that the aggregate particle size formed after crushing meets the grading design requirements of permeable concrete. For example, the particle size of ceramic fragments after crushing is controlled between 5-15mm, and the particle size of glass waste is controlled between 3-10mm. In addition, the surface of glass waste needs to be specially roughened. Mechanical sandblasting can be used to form a tiny concave-convex texture on the glass surface to enhance its bonding with other materials. When using nano silicon dioxide, before ultrasonic vibration treatment, pre-mix the nano silicon dioxide with a small amount of dispersant solution, and the dispersant can be sodium hexametaphosphate, and the amount is 0.5%-1% of the mass of the nano silicon dioxide. The pre-mixing process adopts low-speed stirring, the stirring speed is controlled at 10-20 rpm, and the stirring time is 2-3 minutes, so that the nano silicon dioxide is evenly dispersed in the dispersant solution to form a suspension, and then the suspension is added to the cement matrix for ultrasonic vibration treatment, which can further improve the dispersion effect of the nano silicon dioxide in the cement matrix, avoid the occurrence of agglomeration, and is more conducive to the formation of a stable chemical bond between it and the cement hydration product, thereby improving the strength and durability of the concrete.
[0036] When the recycled aggregate and nano-reinforced materials are mixed with a high-efficiency mixer, the shape and angle of the mixing blades are specially designed. The mixing blades are designed with a forward-inclined arc, and the angle between the blades and the mixing shaft is 30-45 degrees. This design can generate greater shear force and lifting force during the mixing process, so that the materials form a compound movement of up and down rolling and lateral convection in the mixing drum, ensuring that the recycled aggregate and nano-reinforced materials reach a more uniform mixing state in a shorter time. At the same time, during the mixing process, compressed air is introduced into the mixing drum every 2-3 minutes, with a compressed air pressure of 0.2-0.4MPa and a ventilation time of 10-15 seconds. Through the disturbance of the airflow, the possible agglomeration of materials can be further broken and the mixing uniformity can be improved.
[0037] Before adding the self-repairing microcapsules to concrete, they are first coated with biodegradable polyvinyl alcohol. The coating process uses a spray drying method to spray the self-repairing microcapsule suspension into a hot air flow through a nozzle. The hot air temperature is controlled at 120-150°C, so that the polyvinyl alcohol quickly solidifies on the surface of the microcapsules to form a thin film. The coated microcapsules can not only be better dispersed in the concrete, but also effectively prevent the microcapsules from being destroyed prematurely during the concrete molding process, ensuring that they can play a repair role in time when microcracks appear in the concrete, thereby extending the service life of the concrete.
[0038] The temperature and humidity control in the curing room adopts a zone control method. Different temperature and humidity sensors and adjustment devices are set according to the different positions of the concrete specimens. For example, in the area near the entrance of the curing room, due to the relatively fast loss of heat and moisture, a temperature compensation device is set to make its temperature 1-2°C higher than the central area of the curing room, and the humidity is 5%-10% higher, to ensure that the concrete at different positions in the entire curing room can be cured under suitable temperature and humidity conditions. At the same time, during the curing process, the air in the curing room is regularly ventilated, with a ventilation frequency of once every 4-6 hours, and each ventilation volume is 10%-15% of the total volume of the curing room, so as to remove harmful gases that may accumulate in the curing room, such as carbon dioxide, and provide a good environment for the hydration reaction of concrete.
[0039] The specific parameters of the concrete production steps are shown in the following table:
[0040]
[0041] The parameters of the ratio of recycled aggregate to prepared raw materials are shown in the following table:
[0042] Specific embodiment 2:
[0044] like Figure 1-3 As shown, the modification process includes the following steps:
[0045] Sp1. Surface modification treatment steps of recycled aggregate: select waste concrete, brick and tile waste, ceramic fragments and glass waste, and thoroughly clean them to remove dirt and grease attached to the surface. During the cleaning process, use a combination of high-pressure water flow and physical brushing to ensure that the surface of each particle is clean. Soak the cleaned aggregate in a hydrochloric acid solution with a concentration of 5% to 10% for acid etching to remove the residual cement slurry layer on the surface of the aggregate, peel off the excess cement layer through chemical reaction, and improve the surface microstructure of the aggregate. The acid etching time is 30 to 60 minutes, and the temperature is controlled within the normal temperature range to prevent damage to the aggregate due to excessive reaction. After acid etching, place the aggregate in a high temperature environment of 350°C to 500°C for heat treatment for 1 to 2 hours. Through high temperature treatment, remove moisture and residual harmful substances in the aggregate, and further enhance the surface hardness of the aggregate, and improve the bonding strength between the recycled aggregate and the cement matrix;
[0046] SP2. Preparation steps of nano-reinforced materials: Nano-reinforced materials can be selected from nano-silicon dioxide, nano-clay and nano-carbon tubes. When nano-silicon dioxide is selected, it forms a stable hydration product with the cement matrix through good surface activity to enhance the strength and durability of concrete. Ultrasonic vibration treatment technology is used to ensure that nano-silicon dioxide and the cement matrix are evenly dispersed. The ultrasonic power is 200-600W, the vibration time is 3 to 5 minutes, the mass ratio of nano-silicon dioxide is 0.5% to 2% of the cement matrix, the mass ratio of nano-clay is 0.1% to 0.5% of the cement matrix, and the mass ratio of nano-carbon tubes is 0.05% to 0.2% of the cement matrix;
[0047] SP3, mixing steps of recycled aggregate and nano-reinforced material: recycled aggregate and nano-reinforced material are mixed by high-efficiency mixer, the mixing time is 5 to 10 minutes, and the mixing speed is 30 to 50 rpm. An intelligent mixing optimization system is established to assist the mixing of recycled aggregate and nano-reinforced material. The intelligent mixing system automatically adjusts the material ratio according to the two environmental conditions of temperature change and precipitation through machine learning and multi-objective optimization algorithm to ensure that the permeable concrete has the best comprehensive performance. The intelligent mixing optimization system collects temperature and precipitation data through temperature sensors and rainfall sensors in real time, analyzes environmental data through machine learning algorithms and optimization decision algorithms, and calculates the appropriate material ratio. Self-repairing microcapsules are added to the concrete. When microcracks appear in the concrete, the microcapsules rupture and release the repair agent, which reacts with the cement matrix to repair the cracks and extend the service life of the concrete.
[0048] SP4. The mixed material produced by mixing the recycled aggregate and nano-reinforced material in SP3 is formed through a standard template with a mold size of 300mm×300mm×50mm. A vibration table is used for vibration compaction with a vibration frequency of 20-30Hz and a vibration time of 30 seconds to 1 minute to ensure that the surface of the formed concrete is flat and there are no pores inside. The formed concrete is placed in a curing room with controlled temperature and humidity for curing. The curing temperature should be maintained between 20℃ and 30℃, and the humidity should be controlled at more than 90%. The curing time is 7 to 14 days. During this period, the hardening progress and strength growth of the concrete are monitored. A temperature control curing system is used to automatically adjust the temperature and humidity, accelerate the hydration reaction, and improve the strength of the concrete. During the curing period, a temperature and humidity sensor is used to monitor the internal temperature and humidity of the concrete, and the curing conditions are adjusted in real time.
[0049] SP5. Use the water permeability coefficient test method to test the permeability of permeable concrete. During the test, place the concrete sample in a water leaker, measure the time for water to pass through the concrete, calculate the water permeability coefficient, and ensure that the permeability meets the national standards. Then, conduct a compressive strength test according to the national standards. The compressive strength of the test sample should be greater than 25MPa. During the test, use a hydraulic testing machine to apply pressure to the standard specimen until it is destroyed, and record the maximum bearing capacity. Place the sample in a freeze-thaw test box and perform 25 freeze-thaw cycles to observe the mass loss rate and frost resistance changes of the sample. At the same time, monitor the crack width and crack extension to ensure the long-term stability of permeable concrete in cold areas.
[0050] After acid etching, the recycled aggregate is further modified by plasma treatment technology. The plasma treatment power is 100-300W and the treatment time is 10-20 minutes. The plasma treatment increases the surface active groups and improves the bonding strength with the nano-reinforcement material and the cement matrix.
[0051] The nano-reinforced material also includes a nano-metal oxide mixture, which is composed of nano-zinc oxide and nano-magnesium oxide in a mass ratio of 1:1-3:1. The total mass ratio of the mixture in the concrete is 0.1%-0.3% of the cement matrix, which improves the concrete's anti-ultraviolet aging performance.
[0052] In the mixing step of recycled aggregate and nano-reinforcement material, a bio-based additive is added, the bio-based additive is sodium lignin sulfonate and can also be cellulose ether, with a mass ratio of 0.02%-0.1% of the cement matrix, to improve the working performance of concrete and enhance its environmental friendliness.
[0053] The intelligent mixing optimization system can automatically adjust the content of nano-titanium dioxide in the nano-reinforced material according to the ultraviolet intensity data. The ultraviolet intensity data is collected by the ultraviolet sensor. When the ultraviolet intensity increases, the nano-titanium dioxide content is increased to enhance the ultraviolet resistance of the concrete. The content adjustment range is 0.05%-0.15% of the cement matrix mass ratio.
[0054] The repair agent in the self-repairing microcapsule contains polymer emulsion and inorganic mineral material. The polymer emulsion is acrylic emulsion and the inorganic mineral material is wollastonite powder. The mass ratio of the two is 2:1-3:1, which can more effectively repair concrete microcracks and enhance the strength of the repaired part.
[0055] A photocatalytic purification device is installed in the curing room. During the curing process, the concrete surface is photocatalytically treated to remove pollutants on the surface. The photocatalytic purification device uses nano-titanium dioxide photocatalyst, and the wavelength of the ultraviolet light source is 250-350nm.
[0056] During the concrete molding process, a layer of release agent is coated on the inner surface of the mold. The release agent is a water-based fluorocarbon release agent, which effectively reduces the adhesion between the concrete and the mold and ensures the integrity and smoothness of the concrete surface after molding.
[0057] 5%-10% fly ash is added to the cement matrix, and the average particle size is 10 μm. Specific embodiment three:
[0059] The entire concrete preparation process mainly includes the following stages:
[0060] Raw materials preparation stage:
[0061] Recycled aggregate collection and pretreatment: Obtain waste concrete, brick and tile waste, ceramic fragments and glass waste from construction waste recycling stations, use special aggregate screening equipment to preliminarily classify the collected materials according to particle size, and screen out aggregate particles with a particle size range of 5-20mm. Then, put these aggregates into a large cleaning pool, turn on the high-pressure water flow cleaning device, set the water flow pressure to 3-5MPa, and use a mechanical scrubbing device to ensure that the dirt and grease on the surface of each aggregate are completely removed. The cleaned aggregates are dried in a naturally ventilated environment for 24-48 hours to remove excess moisture on the surface.
[0062] Preparation of nano-reinforced materials: For nano-silicon dioxide, products with an average particle size of 20-50nm are selected. Place the nano-silicon dioxide powder in a special dispersion container, add an appropriate amount of dispersant (sodium hexametaphosphate, the amount is 0.8% of the mass of nano-silicon dioxide) and deionized water, and prepare a suspension with a concentration of 10%-15%. Place the suspension in an ultrasonic cleaner, set the ultrasonic power to 400W, and the vibration time to 4 minutes to evenly disperse the nano-silicon dioxide. For nano-clay and nano-carbon tubes, the same pretreatment is performed to ensure that there is no agglomeration. The average particle size of nano-clay is controlled at 50-100nm, and the length of nano-carbon tubes is 5-20μm and the diameter is 10-50nm.
[0063] Preparation of other materials: Use silicate cement with a grade of 42.5 as the cement matrix, the water reduction rate of the polycarboxylate water reducer is 25%-35%, the purity of the sodium dodecylbenzene sulfonate surfactant is above 90%, and ordinary drinking water is used.
[0064] Surface modification of recycled aggregate:
[0065] Acid etching: Soak the dried recycled aggregate in a hydrochloric acid solution with a concentration of 8%. The volume of the solution must completely cover the aggregate. The etching time is 45 minutes, and the temperature is maintained at about 25°C. During the etching process, use a stirring device to slowly stir at a speed of 15-20 rpm to ensure uniform etching. After the etching is completed, immediately rinse the aggregate with a large amount of clean water until the pH value of the rinse water reaches 6-7.
[0066] Heat treatment: The acid-etched aggregate is placed in a resistance heating furnace for heat treatment. The furnace temperature is raised to 400°C at a heating rate of 10°C / min and maintained at this temperature for 1.5 hours. During the heat treatment process, a small amount of nitrogen is introduced into the furnace with a nitrogen flow rate of 0.5-1m 3 / hour to prevent the aggregate from oxidizing at high temperature. After the heat treatment, let the aggregate cool naturally to room temperature in the furnace.
[0067] Plasma treatment (optional): If plasma treatment technology is used for further modification, the heat-treated aggregate is placed in the reaction chamber of the plasma treatment equipment, the plasma treatment power is set to 200W, the treatment time is 15 minutes, and the treatment gas is a mixture of oxygen and argon. The oxygen flow rate is 20-30mL / min, and the argon flow rate is 80-100mL / min. More active groups are formed on the aggregate surface through plasma treatment.
[0068] Material mixing and intelligent regulation:
[0069] Intelligent mixing system construction: The intelligent mixing optimization system consists of a data acquisition module, a data analysis and processing module, and an execution control module. The data acquisition module is connected to a temperature sensor (accuracy of ±0.5℃), a rainfall sensor (resolution of 0.1mm), and an ultraviolet sensor (measuring range of 280-400nm, accuracy of ±5%), which are installed at the outdoor environmental monitoring point and indoor raw material storage area of the concrete preparation workshop respectively. The data analysis and processing module adopts a neural network model based on a deep learning algorithm, and is pre-trained using a large amount of concrete performance test data under different environmental conditions. It can accurately predict the performance indicators of permeable concrete under different material ratios based on the collected environmental data, and calculate the optimal material ratio through the optimization decision algorithm. The execution control module is connected to the control system of the raw material conveying equipment and the mixer, and automatically adjusts the conveying amount of each raw material according to the calculation results.
[0070] Mixing and stirring: Add the recycled aggregate and nano-reinforced material into the high-efficiency mixer according to the predetermined proportion. The inner wall of the mixer drum is provided with a special wear-resistant coating to reduce the wear and material residue during the mixing process. The mixing blade adopts a double-layer spiral structure, the upper blade is left-handed, and the lower blade is right-handed. When mixing, the material can form a composite motion of up and down convection and lateral shear. Start the mixer and stir at a low speed of 20 rpm for 2 minutes to make the materials initially mixed evenly, then gradually increase the speed to 40 rpm, and the stirring time is 8 minutes. During the mixing process, the intelligent mixing system automatically adjusts the content of nano-titanium dioxide in the nano-reinforced material and the proportion of other materials according to the real-time collected environmental data. For example, when the ultraviolet intensity exceeds 100μW / cm 2 At the same time, compressed air was introduced into the mixing drum once every 3 minutes with a compressed air pressure of 0.3 MPa and a ventilation time of 12 seconds to further promote the dispersion of the materials. In the last 2 minutes of stirring, a bio-based additive (sodium lignin sulfonate) was added with a mass ratio of 0.06% of the cement matrix, and stirring was continued until uniform.
[0071] Concrete forming and curing:
[0072] Molding: Pour the mixed materials into a standard steel mold with a size of 300mm×300mm×50mm. The inner surface of the mold is pre-coated with a layer of water-based fluorocarbon release agent with a coating thickness of 0.05-0.1mm. Place the mold on a vibration table with a vibration frequency of 25Hz and a vibration time of 45 seconds to compact the concrete material in the mold, ensuring that the surface is flat and there are no pores inside.
[0073] Curing: After forming, the concrete specimens are immediately transferred to the special curing rack in the curing room. The temperature control system of the curing room adopts an intelligent constant temperature device, which monitors the temperature in real time through multiple temperature sensors distributed in the room. When the temperature is lower than 20℃, the heating device (electric heating wire power is 5-10kW) is started, and when the temperature is higher than 30℃, the refrigeration air conditioner (cooling capacity is 3-5 horsepower) is turned on to keep the curing temperature between 20-30℃. The humidity control system works together through the ultrasonic humidifier and the exhaust fan. When the humidity is lower than 90%, the humidifier automatically starts to increase the indoor humidity. When the humidity is higher than 95%, the exhaust fan is turned on to discharge some moisture to ensure that the humidity is stable between 90% and 95%. During the curing period, the temperature and humidity inside the concrete are monitored in real time using temperature and humidity sensors (temperature accuracy is ±0.3℃, humidity accuracy is ±3%), and the data is transmitted to the central control system of the curing room. The central control system automatically adjusts the curing conditions according to the set curing curve. At the same time, a photocatalytic purification device is installed in the curing room. The nano-titanium dioxide photocatalyst in the device is loaded on a honeycomb ceramic carrier. The ultraviolet light source uses a UVC lamp with a wavelength of 300nm and a power of 30-50W. During the curing process, the concrete surface is photocatalytically treated to remove possible pollutants. The curing time is 10-12 days. During this period, the hardening progress and strength growth of the concrete are tested regularly (every 2 days), and non-destructive detection methods (such as rebound hammer test) are used to preliminarily evaluate the strength development of the concrete.
[0074] Performance testing and evaluation:
[0075] Water permeability coefficient test: After the curing is completed, take out the concrete sample from the curing room and put it into a standard water permeability coefficient test device (leakage tester). The water level of the test device is maintained at 100mm. The time it takes for water to pass through the concrete sample is measured, and the water permeability coefficient is calculated according to the formula to ensure that the permeability meets the national standards. The water permeability coefficient is required to be greater than 0.5mm / s.
[0076] Compressive strength test: Make concrete compressive strength test specimens (size 100mm×100mm×100mm) in accordance with national standards, use a hydraulic testing machine to apply pressure to the specimen, control the loading rate at 0.5-1MPa / s until the specimen is destroyed, record the maximum bearing capacity, and the compressive strength of the test sample should be greater than 25MPa.
[0077] Freeze-thaw cycle test: Put the concrete sample into the freeze-thaw test box, set the freeze-thaw cycle number to 25 times, the freezing temperature to -20℃, the melting temperature to 20℃, and each freezing and melting time to 4 hours. During the freeze-thaw cycle, regularly (every 5 cycles) observe the mass loss rate and frost resistance changes of the sample, and use a high-precision microscope to monitor the crack width and crack extension to ensure the long-term stability of permeable concrete in cold areas. The mass loss rate is required to be no more than 5%, and the loss of compressive strength after freeze-thaw cycles is no more than 20%. Specific embodiment four:
[0079] The above preparation method can be summarized as follows:
[0080] 1. Raw materials and proportions Recycled aggregates: Use waste concrete, bricks and tiles and other waste materials, which are treated with acid, heat and plasma to improve surface properties and enhance bonding with the cement matrix, meeting the needs of environmental protection and cost reduction.
[0081] Nano-reinforcement materials: Reinforcement materials such as nano-silica and nano-titanium oxide help to improve the strength, UV resistance and durability of concrete. Ultrasonic treatment ensures uniform dispersion and enhancement. Cement matrix and chemical additives: Portland cement and additives such as polycarboxylate water reducers and sodium dodecylbenzene sulfonate improve the workability, strength and adhesion of concrete.
[0082] 2. Process innovation
[0083] Intelligent Mixing Optimization System: By real-time monitoring of environmental factors, it automatically adjusts the material ratio to ensure the best performance of concrete under different climatic conditions.
[0084] Self-repairing technology: repair concrete micro cracks through microcapsules to extend service life.
[0085] Photocatalytic purification: Nano-titanium dioxide photocatalyst helps the concrete surface to self-clean and improves its anti-pollution ability.
[0086] 3. Performance Testing
[0087] The permeability test meets the standards for permeable concrete, the compressive strength is ≥25MPa, the freeze-thaw performance meets the standards for severe cold areas, the addition of nanomaterials enhances UV resistance, the multiple material system improves the comprehensive performance of permeable concrete, the intelligent mixing and real-time adjustment system improves the adaptability and stability of the material, and the self-repairing technology and photocatalytic treatment improve the durability and environmental friendliness of the concrete.
[0088] Further experimental data are as follows:
[0089]
[0090]
[0091] The following is the experimental data table of finished concrete test:
[0092]
[0093]
[0094] Specific embodiment five:
[0096] The following provides a comparative example of the permeable concrete obtained by the preparation method and the existing concrete:
[0097] Comparison 1: Traditional permeable concrete vs modified recycled aggregate and nano-reinforced material permeable concrete
[0098]
[0099] Specific embodiment six:
[0101] like Figure 1-3 As shown, based on the above embodiments, the following supplements can also be made. In the preparation process of nano-reinforced materials, nano-silicon dioxide and nano-clay are tried to be composite-modified. Through the chemical coating process, nano-silicon dioxide is evenly coated on the surface of nano-clay particles to form a composite nano-material with a core-shell structure. This composite structure can not only combine the high active surface of nano-silicon dioxide with the good dispersibility and filling of nano-clay, but also build a more stable and continuous reinforcing phase network in the cement matrix, significantly improving the strength and toughness of concrete. For example, the nano-reinforced material after composite modification can increase the 28-day compressive strength of concrete by 15%-20% and the flexural strength by 10%-15%.
[0102] Optimization of micro-pore structure: In the step of mixing recycled aggregate and nano-reinforcement material, bio-based polysaccharides are introduced. The substances are evenly dispersed during the concrete mixing process and interact with cement hydration products during the hardening process to form a microporous structure of specific size and distribution inside the concrete. These micropores can not only ensure the good water permeability of the concrete, but also prevent the invasion of harmful media to a certain extent, thereby improving the durability of the concrete. By controlling the addition amount of bio-based polysaccharides and the reaction conditions, the pore size range of the micropores can be precisely controlled between 0.1-10μm, and the porosity can be maintained at 10%-15%, thereby increasing the impermeability of the concrete by 2-3 times.
[0103] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the statement "comprising a reference structure" do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0104] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A permeable concrete prepared from modified recycled aggregate and nano-reinforced material, characterized in that: The raw materials include recycled aggregate, nano-reinforced material, cement matrix, water reducer, surfactant and water; the recycled aggregate includes waste concrete, brick and tile waste, ceramic fragments and glass waste; the nano-reinforced material includes nano-silicon dioxide, nano-clay, nano-titanium oxide and nano-carbon tube; the particle surface of the recycled aggregate is modified; the mass ratio of the recycled aggregate to the nano-reinforced material is 1:0.05 to 1:0.15; the cement matrix is silicate cement; the water reducer is a polycarboxylate water reducer; the surfactant is sodium dodecylbenzene sulfonate; the recycled aggregate, nano-reinforced material and water are used as raw materials ... The mass ratio of the material, cement matrix, water reducer, surfactant and water is 1:0.1 to 1:0.5:0.3 to 0.5:0.05 to 0.1:0.02 to 0.05:0.4 to 0.
6. When the recycled aggregate is taken as 1 part as the reference mass, the amount of the nano-reinforcement material is 0.1-0.5 part, the amount of the cement matrix is 0.3-0.5 part, the amount of the water reducer is 0.05-0.1 part, and the amount of the sodium dodecylbenzene sulfonate surfactant is 0.02-0.05 part. The particle surface of the recycled aggregate is modified, and the modification process includes the following steps: Sp1, surface modification treatment steps of recycled aggregate: select waste concrete, brick and tile waste, ceramic fragments and glass waste, and thoroughly clean them to remove dirt and grease attached to the surface. During the cleaning process, use a combination of high-pressure water flow and physical brushing to ensure that the surface of each particle is clean. Soak the cleaned aggregate in a hydrochloric acid solution with a concentration of 5% to 10% for acid etching for 30 to 60 minutes. After acid etching, place the aggregate in a high temperature environment of 350°C to 500°C for heat treatment for 1 to 2 hours. Through high temperature treatment, remove moisture and residual harmful substances in the aggregate; SP2, preparation steps of nano-reinforced materials: the nano-reinforced materials can be selected from nano-silicon dioxide, nano-clay and nano-carbon tubes. When nano-silicon dioxide is selected, it forms a stable hydration product with the cement matrix through good surface activity to enhance the strength and durability of concrete. Ultrasonic vibration treatment technology is used to ensure that the nano-silicon dioxide and the cement matrix are evenly dispersed. The ultrasonic power is 200-600W, and the vibration time is 3 to 5 minutes. The mass ratio of the nano-silicon dioxide is 0.5% to 2% of the cement matrix, the mass ratio of the nano-clay is 0.1% to 0.5% of the cement matrix, and the mass ratio of the nano-carbon tube is 0.05% to 0.2% of the cement matrix; SP3, the step of mixing the recycled aggregate and the nano-reinforced material: the recycled aggregate and the nano-reinforced material are stirred by a high-efficiency mixer during mixing, the stirring time is 5 to 10 minutes, and the stirring speed is 30 to 50 rpm. An intelligent mixing optimization system is established to assist the mixing of the recycled aggregate and the nano-reinforced material. The intelligent mixing system automatically adjusts the material ratio according to the two environmental conditions of temperature change and precipitation through machine learning and multi-objective optimization algorithms. The intelligent mixing optimization system collects temperature and precipitation data in real time through temperature sensors and rainfall sensors, analyzes environmental data through machine learning algorithms and optimization decision algorithms, and adds self-repairing microcapsules to the concrete. When microcracks appear in the concrete, the microcapsules rupture, release the repair agent, and react with the cement matrix to repair the cracks; SP4, the mixed material produced by mixing the recycled aggregate and the nano-reinforced material in SP3 is formed through a standard template, the size of the mold is 300mm×300mm×50mm, and a vibration table is used for vibration compaction, the vibration frequency is 20-30Hz, and the vibration time is 30 seconds to 1 minute. The formed concrete is placed in a curing room with controlled temperature and humidity for curing. The curing temperature should be maintained between 20°C and 30°C, and the humidity is controlled at more than 90%. The curing time is 7 to 14 days. During this period, the hardening progress and strength growth of the concrete are monitored, and a temperature control curing system is used to automatically adjust the temperature and humidity, accelerate the hydration reaction, and improve the strength of the concrete. During the curing period, a temperature and humidity sensor is used to monitor the internal temperature and humidity of the concrete, and the curing conditions are adjusted in real time; SP5. Use the water permeability coefficient test method to test the permeability of permeable concrete. During the test, place the concrete sample in a water leaker, measure the time for water to pass through the concrete, calculate the water permeability coefficient, and ensure that the water permeability meets the national standards. Then, conduct a compressive strength test according to the national standards. The compressive strength of the test sample should be greater than 25MPa. During the test, use a hydraulic testing machine to apply pressure to the standard specimen until it is destroyed, and record the maximum bearing capacity. Place the sample in a freeze-thaw test box and perform 25 freeze-thaw cycles to observe the mass loss rate and frost resistance changes of the sample, and monitor the crack width and crack extension at the same time.
2. The permeable concrete prepared from modified recycled aggregate and nano-reinforced material according to claim 1, characterized in that: After acid etching, the recycled aggregate is further modified by plasma treatment technology. The plasma treatment power is 100-300W and the treatment time is 10-20 minutes. The plasma treatment increases the surface active groups and improves the bonding strength with the nano-reinforced material and the cement matrix.
3. The permeable concrete prepared by modified recycled aggregate and nano-reinforced material according to claim 1, characterized in that: The nano-reinforced material also includes a nano-metal oxide mixture, which is composed of nano-zinc oxide and nano-magnesium oxide in a mass ratio of 1:1-3:1, and the total mass ratio in concrete is 0.1%-0.3% of the cement matrix, thereby improving the concrete's anti-ultraviolet aging performance.
4. The permeable concrete prepared by modified recycled aggregate and nano-reinforced material according to claim 1, characterized in that: In the step of mixing the recycled aggregate and the nano-reinforced material, a bio-based additive is added. The bio-based additive is sodium lignin sulfonate and can also be cellulose ether, and the mass ratio is 0.02%-0.1% of the cement matrix.
5. The permeable concrete prepared by modified recycled aggregate and nano-reinforced material according to claim 1, characterized in that: The intelligent mixing optimization system can automatically adjust the content of nano-titanium dioxide in the nano-reinforced material according to ultraviolet intensity data collected by an ultraviolet sensor. When the ultraviolet intensity increases, the nano-titanium dioxide content is increased to enhance the anti-ultraviolet ability of concrete. The content adjustment range is 0.05%-0.15% of the cement matrix mass ratio.
6. The permeable concrete prepared from modified recycled aggregate and nano-reinforced material according to claim 1, characterized in that: The repairing agent in the self-repairing microcapsule contains polymer emulsion and inorganic mineral material, the polymer emulsion is acrylic ester emulsion, and the inorganic mineral material is wollastonite powder, and the mass ratio of the two is 2:1-3:
1.
7. The permeable concrete prepared from modified recycled aggregate and nano-reinforced material according to claim 1, characterized in that: The curing room is provided with a photocatalytic purification device, which performs photocatalytic treatment on the concrete surface during the curing process to remove pollutants on the surface. The photocatalytic purification device uses a nano titanium dioxide photocatalyst, and the wavelength of the ultraviolet light source is 250-350nm.
8. The permeable concrete prepared from modified recycled aggregate and nano-reinforced material according to claim 1, characterized in that: During the concrete forming process, a layer of release agent is coated on the inner surface of the mold, and the release agent is a water-based fluorocarbon release agent.
9. The permeable concrete prepared by modified recycled aggregate and nano-reinforced material according to claim 1, characterized in that: The cement matrix is mixed with 5%-10% fly ash, and the average particle size is 10 μm.
Citation Information
Patent Citations
Pervious concrete based on recycled aggregate loaded nano TiO2 and preparation method thereof
CN118955046A
Nano reinforcing method for recycled aggregate concrete
CN102092993A
Environment-friendly and energy-saving building material and preparation method thereof
CN108558311A
Recycled aggregate pervious concrete, and preparation method and application thereof
CN110510949A
Nano silicon dioxide and basalt fiber synergistically enhanced recycled concrete and preparation method thereof
CN114656206A
Cited By
Carbon nanotube-GO synergistically modified inorganic multi-compound gelling agent and preparation method thereof
CN121044841A
Reinforced recycled aggregate concrete and preparation method thereof
CN121426513A